Rare male cancers: Effect of social deprivation on a cohort of penile cancer patients. (May 2021) - Rewhorn, Matthew J; Shin, Je Song; Hendry, Jane; McKay, Alastair; Vint, Ross; Leung, Hing Y; Meddings, Robert N; Hendry, David S; Fraser, Michael
Background: Penile cancer is a rare disease, with approximately 600 cases diagnosed every year in the UK. In this study, we assessed the impact of social deprivation on penile cancer, concentrating on incidence, disease factors, surgical treatment and mortality within our 'Supranetwork' population. Methods: All cases of penile cancer in the West of Scotland were identified from the uro-oncology multidisciplinary team meetings over a 10-year period covering January 2008 to December 2017. Patients underwent treatment within the remit of a centralised service, and social deprivation was determined using the Scottish Index of Multiple Deprivation (SIMD), which is the Scottish government's official tool to identify areas of multiple deprivations. Results: A total of 278 patients were identified, with an age range of 27–97 years ( M =64 years). The incidence of penile cancer in SIMD category 1 (most deprived) is 7.2/100, 000 population at risk compared to 2.8/100, 000 population at risk in SIMD category 5 (least deprived). Histologically, a higher proportion of aggressive grade 3 cancers (45% vs. 16%, p =0.03) and more advanced N2/N3 nodal disease (63% vs. 33%, p =0.04) was found in SIMD category 1 compared to SIMD category 5, suggesting higher incidence of delayed presentation with more advanced and aggressive disease in the most deprived populations. Conclusions: The level of social deprivation shows a significant association with penile cancer incidence, tumour grade and stage at time of diagnosis, with a resulting disproportionate impact on morbidity and mortality in the most deprived cohort of patients. Public awareness and efforts to increase earlier diagnoses of penile cancer in these 'hard to reach' men should be an important step in improving overall outcomes from penile cancer.